2018
DOI: 10.1021/acsami.8b00430
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Annealing Controlled Crystal Growth and Photovoltaic Performance of Bismuth Triiodide Embedded in Mesostructured Configurations

Abstract: Low stability of organic-inorganic lead halide perovskite and toxicity of lead (Pb) still remain a concern. Therefore, there is a constant quest for alternative nontoxic and stable light-absorbing materials with promising optoelectronic properties. Herein, we report about nontoxic bismuth triiodide (BiI) photovoltaic device prepared using TiO mesoporous film and spiro-OMeTAD as electron- and hole-transporting materials, respectively. Effect of annealing methods (e.g., thermal annealing (TA), solvent vapor anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…www.advancedsciencenews.com was used to improve the film quality and reproducibility of BiI 3 . [61] The film-based device showed a PCE of 0.5% with TiO 2 mesostructured architecture employing 2,2′,7,7′-tetrakis(N,Ndi-p-methoxyphenylamine)-9,9′-spirobifluorene (Spiro-OMeTAD) as the HTM. These results indicated that the V oc of BiI 3 -based solar cells is always less than 0.4 V. The V oc loss is much higher than that of lead-containing perovskite solar cell.…”
Section: Solar Cellsmentioning
confidence: 98%
“…www.advancedsciencenews.com was used to improve the film quality and reproducibility of BiI 3 . [61] The film-based device showed a PCE of 0.5% with TiO 2 mesostructured architecture employing 2,2′,7,7′-tetrakis(N,Ndi-p-methoxyphenylamine)-9,9′-spirobifluorene (Spiro-OMeTAD) as the HTM. These results indicated that the V oc of BiI 3 -based solar cells is always less than 0.4 V. The V oc loss is much higher than that of lead-containing perovskite solar cell.…”
Section: Solar Cellsmentioning
confidence: 98%
“…[11,16] Several strategies for retarding the crystal growth rate of Pb perovskite during annealing,s uch as ionic liquid addition, [37] hot-casting method, [38] and solvent annealing [39][40][41][42] have been reported. [11,16] Several strategies for retarding the crystal growth rate of Pb perovskite during annealing,s uch as ionic liquid addition, [37] hot-casting method, [38] and solvent annealing [39][40][41][42] have been reported.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The present results would pave the way for exploiting high‐quality photodetecting devices based on large‐area 2DLMs films. What is more, the synthesized BiI 3 films with remarkable response to visible light are also equipped with great potentials in the fields of sensors, solar cells, photovoltaic, photocatalysis, and bismuth‐halide perovskites …”
mentioning
confidence: 99%